PEMBUATAN APLIKASI TRY OUT SIMULASI PERSIAPAN SNMPTN - Tanti Kristanti; Devriena Ocktara (Jurusan Teknik Informatika, Fakultas Teknologi Industri, Universitas Islam Indonesia, 2012)
One of informal educations is tutoring institution that provides services for students to improve learning and achievement in facing “Seleksi Nasional Masuk Perguruan Tinggi Negeri (SNMPTN)”. The institution help some students in accordance with SNMPTN try out, especially in measuring their abilities in answering the SNMPTN questions and review the results. SSC is an informal educational institution that appropriate tryout preparation for their students. SSC also provide an online tryout facility on their website, but it is only for exercise, not for giving any further information about SNMPTN test. This study is purposed to make a SNMPTN tryout simulation application based on standalone to help students access the tryout exercise easier, without internet service. To make this application more similar into the real SNMPTN test by providing many frequently ask questions that had been commonly tested. It also can be updated and report allowed to get the result, whether the student can pass the standard of their own interest for college majoring test or not, accordance to their score which is showed by details on each subject they chose. This application is also be able to update the information of every PTN in Indonesia.The SNMPTN Tryout Simulation Application Preparation will be build by Java programming language, MySQL as data base and netbeans as editor. The conclusion obtained is the end result of making the SNMPTN tryout simulation application preparation has reached the goal.